Linear Vary-Chap Topside Electron Density Model with Topside Sounder and Radio-Occultation Data - dos Santos Prol, Fabricio [UNESP]; Themens, David R.; Hernández-Pajares, Manuel; de Oliveira Camargo, Paulo [UNESP]; de Assis Honorato Muella, Marcio Tadeu (Springer Nature, 2019)
The Linear Vary-Chap function has received increased attention in describing the topside ionosphere due to its good performance for predicting and extrapolating radio-occultation (RO) electron density ionospheric profiles. The systematic increase in the scale height is consistent with first principles corresponding to the increase in the electron temperature; however, the altitude where the linear scale height approximation does not stay valid has not been explicitly discussed in the literature. In order to demonstrate up to what extent the linear behavior of the scale height is still valid, this work analyzes more than 50,000 manually scaled ionospheric profiles measured by topside sounders on board Alouette and International Satellites for Ionospheric Studies satellites. Based on this initial analysis, a new topside model is proposed to take into consideration the nonlinear behavior of the topside scale height. The proposed climatological model, a fit of spherical harmonics to parameters derived from topside RO profiles, is used to predict topside sounder measurements. An assessment of the predicted, RO-derived, topside is carried out and the experimental results are discussed in order to show the viability of extrapolating RO ionospheric profiles for altitudes above the low Earth orbit.
Keywords: Alouette; Chapman function; COSMIC/FORMOSAT-3; Ionospheric profile; ISIS; Scale height